2020
DOI: 10.1111/aogs.13940
|View full text |Cite
|
Sign up to set email alerts
|

Family history and risk of miscarriage: A systematic review and meta‐analysis of observational studies

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…A summary of epidemiological factors and their potential effects on the risk of pregnancy loss are shown in Table 3. [7][8][9][10] Aetiology A 2018 study 11 into RPL aetiology showed only 26% of the patients reviewed had an explained cause, with the rest not given an aetiology or a causative reason.…”
Section: Definition Of Recurrent Pregnancy Lossmentioning
confidence: 99%
“…A summary of epidemiological factors and their potential effects on the risk of pregnancy loss are shown in Table 3. [7][8][9][10] Aetiology A 2018 study 11 into RPL aetiology showed only 26% of the patients reviewed had an explained cause, with the rest not given an aetiology or a causative reason.…”
Section: Definition Of Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Moreover, an increased probability of the same karyotype pattern (recurrent normal or recurrent abnormal) in multiple consecutive abortions was found for RPL patients [ 32 , 33 , 34 ]. In addition, women who miscarry may be more likely to have a family history of miscarriage [ 35 ]. The significance of genetic factors in miscarriage was proven by the six-fold increase in RPL prevalence among first-degree relatives of idiopathic RPL patients in comparison with the general population [ 36 , 37 ].…”
Section: Genetic Causes Of Miscarriagementioning
confidence: 99%
“…There should not be any language barrier while doing the physical and hysteroscopy examination and a proper language translator should be provided. Early bleeding might be associated with miscarriage therefore it is recommended to evaluate thoroughly for the gynecological history of the patients [67][68][69] . Statistic's analysis suggests that out of four women one faces miscarriage issues.…”
Section: Early Pregnancy Issuesmentioning
confidence: 99%